A Reflective Essay Concerning Something Better: The Experiences of Appalachian Rural Trust Schools - Dianna L. Haleman; Alan J. DeYoung (Journal of Research in Rural Education, 2000)
This article employs the philosophy of John Dewey and the experiences ofseveral Appalachian Rural School and Community Trust participants to illustrate potential connections between rural schools that embrace place-situated curricula and the communities that sustain them. The article is not research-based. Rather, it is a reflective essay that discusses ways these specific schools interact with their local communities. While keeping in mind that each Rural Trust school is unique, we suggest possible alliances between other rural schools and communities. We also suggest the need for more empirical research that specifically examines outcomes ofplace-situated curricula for both schools and communities.